2015
DOI: 10.1097/acm.0000000000000603
|View full text |Cite
|
Sign up to set email alerts
|

The Patient-as-Partner Approach in Health Care

Abstract: The prevalence of chronic diseases today calls for new ways of working with patients to manage their care. Although patient-centered approaches have contributed to significant advances in care and to treatments that more fully respect patients' preferences, values, and personal experiences, the reality is that health care professionals still hold a monopoly on the role of healer. Patients live with their conditions every day and are experts when it comes to their own experiences of illness; this expertise shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
133
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(138 citation statements)
references
References 16 publications
0
133
0
5
Order By: Relevance
“…Enrollment of patients diagnosed with depression into care management intervention was 96.5% Baker et al [29]US CareSouth outpatient clinicsEducational material design around body mass index after negative initial feedback regarding topic approach; revised pain assessment“A strong collaborative engagement with the patient is likely necessary to achieve high reliability” Bitton et al [27]Hospital- and community-based primary care teaching practices affiliated with Harvard Medical SchoolClinic “transformation teams” encouraged to include patients as core members“Trainees and patients can be agents of change, and their presence provides added motivation for academic faculty to create and support change” Coulter and Elwyn [20]UK policy efforts to involve public in healthcare processesCommunity-health councils, proposed statutory patient forums and commission for patient and public involvement and health, patient advisory and liaison services in each trust, annual patient surveyNo empirical findings reported DiGioia et al [23]University of Pittsburgh Medical Center, US6-step patient- and family-centered care methodology including using Codesign Toolkit and Improvement Team to close gaps between current and ideal care experiences“Refocuses existing resources around the patient and family rather than fitting patients and families around the physician and system. It makes it possible to take any current state and move the care experience toward the ideal—as defined by patients and families” Fontaine et al [28]Minnesota primary care practicesState PCMH certification standard development included patient-advocacy representatives; published standards include “continuous improvement process that included a quality-improvement committee with active patient recruitment and participation”Patient’s positive experiences with PCMH increased practice leaders’ job satisfaction and trust in the processProcess for using patients as PCMH advisors/getting input on PCMH changes from patient partners on change team all correlated significantly ( P  ≤ 0.01) with practice system change (but not clinical outcomes) [33] Karazivan et al [24]Direction of Collaboration and Patient Partnership at the University of Montreal: Implemented by two primary care teams as of 2014Accompany clinical teams in implementation of care partnership continuous improvement approachResults not yet available Loud et al [30]; also described in Armstrong et al [38]Primary care for people with CKD in UKPatient advisory group actively participate...…”
Section: Resultsmentioning
confidence: 99%
“…Enrollment of patients diagnosed with depression into care management intervention was 96.5% Baker et al [29]US CareSouth outpatient clinicsEducational material design around body mass index after negative initial feedback regarding topic approach; revised pain assessment“A strong collaborative engagement with the patient is likely necessary to achieve high reliability” Bitton et al [27]Hospital- and community-based primary care teaching practices affiliated with Harvard Medical SchoolClinic “transformation teams” encouraged to include patients as core members“Trainees and patients can be agents of change, and their presence provides added motivation for academic faculty to create and support change” Coulter and Elwyn [20]UK policy efforts to involve public in healthcare processesCommunity-health councils, proposed statutory patient forums and commission for patient and public involvement and health, patient advisory and liaison services in each trust, annual patient surveyNo empirical findings reported DiGioia et al [23]University of Pittsburgh Medical Center, US6-step patient- and family-centered care methodology including using Codesign Toolkit and Improvement Team to close gaps between current and ideal care experiences“Refocuses existing resources around the patient and family rather than fitting patients and families around the physician and system. It makes it possible to take any current state and move the care experience toward the ideal—as defined by patients and families” Fontaine et al [28]Minnesota primary care practicesState PCMH certification standard development included patient-advocacy representatives; published standards include “continuous improvement process that included a quality-improvement committee with active patient recruitment and participation”Patient’s positive experiences with PCMH increased practice leaders’ job satisfaction and trust in the processProcess for using patients as PCMH advisors/getting input on PCMH changes from patient partners on change team all correlated significantly ( P  ≤ 0.01) with practice system change (but not clinical outcomes) [33] Karazivan et al [24]Direction of Collaboration and Patient Partnership at the University of Montreal: Implemented by two primary care teams as of 2014Accompany clinical teams in implementation of care partnership continuous improvement approachResults not yet available Loud et al [30]; also described in Armstrong et al [38]Primary care for people with CKD in UKPatient advisory group actively participate...…”
Section: Resultsmentioning
confidence: 99%
“…Current medical education includes patient participation as an important component of the physician-patient relationship. 16 No other studies have examined whether resident and attending physicians’ attitudes about patient empowerment differ. Davis demonstrated that only 41% of providers felt that family member involvement would have a positive effect on the family member-provider relationship.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there has been a shift from the paternalistic, doctor-knows-best model of decision-making to the shared decision-making model. These models have been shown to produce better patient outcomes than their predecessors [789]. …”
Section: Introductionmentioning
confidence: 99%